REKONSTRUKSI HISTORIS TERHADAP PERAN KHALIFAH AL-HAKIM BIAMRILLAH DULAH FATIMIYAH DALAM PERKEMBANGAN PERPUSTAKAAN DAR AL-HIKMAH DI MESIR TAHUN 996-1021 M - Nurdiana, Rima Esni; Laugu, Nurdin (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2017)
This research aims to understand the role of al-Hakim Biamrillah in developing of Dar Al-Hikmah library in Egypt during his leadership as Khalifah Daulah Fatimiyah. The research used a qualitative approach based on literature, both primary and secondary sources. This study found a number of important points related to the development of Dar Al-Hikmah library for the role played by the Khalifah al-Hakim. The first role played by al-Hakim is management of Dar Al-Hikmah library with the appointment of library managers to handle the library collections. The second role is the development of collection through procurement, especially related to the mechanism of purchasing books, both from local and other the countries. The last role concerns the library as a center for the development of science and teaching. As a center of science, this period is marked by the birth of great scientists, such as Ali bin Nu'man and Ibn Killis.